On intrinsic normalizations of semi-non-holonomic hypercomplexes SNGr(1, n, 2n-3) in affine space - Staišienė, Janina (Lietuvos matematikos rinkinys, 1998)
In this paper the differential geometry of semi-non-holonomic hypercomplexes in n-dimensional affine space is constructed in an invariant analytic form. The differential neighbourhoods of first two orders are studied. In some cases the geometrical constructions of intrinsic normalizations (the Cartan normalizations ant the Bortolotti normalizations) are given.